Energy Consumption Analysis of Refrigeration System with Large Temperature Difference in Cooling Water - Zhu Kaikai; Ren Jianxing; Zhang Junjie; Li Mengqi; Ma Libin; Wang Haiwen (Zhileng xuebao)
During operation, the energy consumption of an air conditioning system has a great influence on energy savings of the whole system. Therefore, the development of cooling water technology with a large temperature difference will help reduce energy consumption of air conditioning system. The relationship between the chiller parameters and temperature difference of cooling water is obtained through theoretical analysis and derivation in this paper. In different experimental conditions with different cooling water temperature difference, the energy consumption of the chiller and cooling water pump is analyzed. The results indicate that with an increase in the cooling water temperature difference, the energy consumption of the air-conditioning system decreases gradually, although the energy consumption of the chiller increases gradually. When the temperature difference is 8 ℃, the maximum EER of air conditioning system is 3.173. The energy saving effect of the air conditioning system is obvious when the cooling water temperature difference is 7-9 ℃.